Porous organic polymer with high content of sulfonic acid groups as well as preparation method and application of porous organic polymer
By adsorbing ammonia by porous organic polymers with high content of sulfonic acid groups, the battery poisoning and environmental pollution caused by ammonia residue in ammonia hydrogen fuel cells is solved, and efficient ammonia removal is achieved, ensuring battery performance and environmental protection.
Patent Information
- Application Number
- CN202411431743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
The trace residue of ammonia gas in ammonia hydrogen fuel cells leads to battery poisoning and inactivation, affecting performance, and causing pollution in the environment. The existing porous materials do not perform well in the removal of low concentrations of ammonia gas.
Porous organic polymers with high content of sulfonic acid groups are used to sulfonate after self-polymerization of initiator and crosslinker monomers to form a micromesoporous structure with excellent adsorption properties, and sulfonated by chlorosulfonic acid to form a stable Sulfonic acid groups improve the adsorption and separation capacity of ammonia.
It realizes efficient and stable ammonia adsorption and separation, providing a solution to the removal of low-concentration ammonia gas, ensuring the stability of ammonia hydrogen fuel cell, and improving environmental quality.
Smart Images

Figure CN119306861A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid acid technology, and in particular to a porous organic polymer with a high content of sulfonic acid groups and a preparation method and application thereof. Background Art
[0002] In ammonia-hydrogen fuel cells, the problem of trace residual ammonia (NH3) is particularly critical. Hydrogen produced by the decomposition of NH3 is the main reactant of proton exchange membrane fuel, but the residual low concentration of NH3 will cause the battery to be poisoned and inactivated, thereby greatly reducing the performance of the battery. This poisoning phenomenon is mainly caused by the residual NH3 combining with protons, hindering the normal circulation of protons, affecting the normal operation of ammonia-hydrogen fuel cells. In addition, NH3 is also an important chemical widely used in industry and agriculture, but its release in the atmosphere may cause serious environmental problems such as acid rain and air pollution. NH3 can be transformed into fine particles through atmospheric transmission and enter the respiratory system, increasing the risk of respiratory diseases, especially for people with asthma. The accumulation of NH3 in the environment can also lead to eutrophication of water bodies, trigger algae reproduction, and in severe cases cause hypoxia in water bodies, affecting the survival of aquatic organisms and destroying the ecological balance. Therefore, the development of effective ammonia removal technology is not only crucial to ensure the stability and extend the service life of ammonia-hydrogen fuel cells, but also helps to protect the environment, improve air quality, protect public health and recycle NH3.
[0003] The effective adsorption technology of NH3 has demonstrated its importance in the removal of low-concentration NH3. The high surface area and porosity of porous materials can effectively adsorb NH3. In recent years, various porous solid materials such as molecular sieves, metal organic frameworks (MOFs), porous organic polymers (POPs), etc. have been found to have application prospects for selective adsorption and separation of NH3. Compared with other materials, POPs have the advantages of simple and economical synthesis methods and stable material skeletons. The porous organic polymers with different structures are directly sulfonated by chlorosulfonic acid sulfonation, which can not only obtain super-strong acid solid acid adsorbents, but also modify their skeletons to obtain super-hydrophobic stable frameworks. Structurally, porous polymers modified with sulfonated groups are not easily hydrolyzed and have stable structures. In terms of performance, porous organic polymers with a network structure can load more acidic stable points and have the advantages of high performance and high selectivity.
[0004] Therefore, developing a porous organic polymer that efficiently adsorbs NH3 has a good market prospect. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present application provides a porous organic polymer with a high content of sulfonic acid groups and its preparation method and application. The preparation method of the present application is simple, the reaction conditions are mild, the cost is low, and it is suitable for large-scale production. The porous organic polymer with a high content of sulfonic acid groups prepared by the present application shows good performance and stable circulation capacity in the test of adsorption and separation of ammonia, and has excellent NH3 adsorption performance, selectivity and penetration ability. The present application uses initiator, cross-linking agent monomer to directly sulfonate to obtain a porous organic polymer (PDVB-SO3H-x) modified by sulfonic acid groups after self-polymerization to form micro-mesoporous organic polymers. In the preparation process, divinylbenzene and sodium styrene sulfonate are monomers, tetrahydrofuran, ethyl acetate, etc. are the first solvent, and chlorosulfonic acid is used as a sulfonating agent. In addition, different solvents and initiators form different nanopores and PDVB skeletons, and sulfonation is carried out under ethylene dichloride as a solvent to obtain a porous organic polymer with a high content of sulfonic acid groups with excellent adsorption performance.
[0006] In a first aspect, the present application provides a method for preparing a porous organic polymer with a high content of sulfonic acid groups, using the following technical scheme: A method for preparing a porous organic polymer with a high content of sulfonic acid groups comprises the following steps: S1, mixing the crosslinking agent monomer, the initiator and the first solvent to obtain a first mixed solution; S2, transferring the first mixed solution to a polytetrafluoroethylene-lined reactor for polymerization reaction to obtain a polymerization reaction product; S3, drying the polymerization product at the first temperature to obtain a solid product; S4, dispersing the solid product in a dichloroethane solution to obtain a second mixed solution, adding chlorosulfonic acid to the second mixed solution under ice bath conditions and stirring to obtain a mixture A; S5, washing the mixture A with deionized water and filtering until the pH value of the mixture A is 5-6; when the pH value of the mixture A reaches 5-6, washing the mixture A with dichloroethane; S6. Drying the rinsed mixture A under vacuum to obtain a porous organic polymer with a high content of sulfonic acid groups.
[0007] By adopting the above technical scheme, the porous organic polymer (PDVB-SO3H-x) modified by sulfonic acid group is obtained by directly sulfonating the initiator and crosslinker monomers after self-polymerization to form a micro-mesoporous organic polymer. In the preparation process, divinylbenzene and sodium styrene sulfonate can be used as monomers, tetrahydrofuran, ethyl acetate, etc. can be used as solvents, and chlorosulfonic acid can be used as a sulfonating agent. In addition, different solvents and initiators form different nanopores and PDVB skeletons, and sulfonation is carried out under dichloroethane as a solvent to obtain a porous organic polymer with a high content of sulfonic acid groups with excellent adsorption properties. Step S1 is to mix and stir the crosslinker monomer with the initiator and the first solvent to obtain a first mixed solution. This step is to fully mix the crosslinker monomer, the initiator and the first solvent to prepare for the subsequent polymerization reaction. Step S2 is to transfer the first mixed solution to a lined reactor containing polytetrafluoroethylene for polymerization reaction to obtain a polymerization product. This step is to polymerize the crosslinker monomer in the first mixed solution to form a micro-mesoporous organic polymer. Step S3 is to dry the polymerization product at a first temperature to obtain a solid product. This step is to remove the solvent in the polymerization product to obtain a solid product. Step S4 is to disperse the solid product in a dichloroethane solution to obtain a second mixed solution, add chlorosulfonic acid to the second mixed solution under ice bath conditions and stir to obtain a mixture A. This step is to disperse the solid product in a dichloroethane solution, and then add chlorosulfonic acid for sulfonation reaction to obtain a mixture A. Step S5 is to wash and filter the mixture A with deionized water until the pH value of the mixture A is 5-6; when the pH value of the mixture A reaches 5-6, the mixture A is rinsed with dichloroethane. This step is to remove impurities in the mixture A and obtain a porous organic polymer with a high content of sulfonic acid groups. Step S6 is to dry the rinsed mixture A under a vacuum environment to obtain a porous organic polymer with a high content of sulfonic acid groups. This step is to remove the solvent in the mixture A and obtain a porous organic polymer with a high content of sulfonic acid groups. Through the synergistic effect of the above six steps, the present application successfully prepared a porous organic polymer with a high content of sulfonic acid groups. This polymer showed good performance and stable circulation capacity in the test of adsorption and separation of ammonia, and had excellent NH3 adsorption performance, selectivity and penetration ability. The preparation method of the present application is simple, the reaction conditions are mild, the cost is low, and it is suitable for large-scale production.
[0008] Preferably, in step S1, the crosslinking agent monomer is at least one of divinylbenzene and sodium styrene sulfonate; the initiator is at least one of ferric chloride and azobisisobutyronitrile; and the first solvent is at least one of ethyl acetate and tetrahydrofuran.
[0009] Preferably, in step S1, the mixing and stirring time is 30-100 minutes.
[0010] Preferably, in step S2, the reaction temperature of the polymerization reaction is 100-220° C., and the reaction time of the polymerization reaction is 8-30 hours.
[0011] Preferably, in step S3, the first temperature is 20-25° C., and the drying time is 48-52 hours.
[0012] Preferably, in step S4, the stirring time is 12-15 hours.
[0013] Preferably, in step S4, the drying temperature is 50-80°C.
[0014] In a second aspect, the present application provides a porous organic polymer with a high content of sulfonic acid groups, which adopts the following technical solution: As a general technical concept, the present application also provides a porous organic polymer with a high content of sulfonic acid groups prepared by the above-mentioned method for preparing a porous organic polymer with a high content of sulfonic acid groups, wherein the content of sulfonic acid groups in the porous organic polymer with a high content of sulfonic acid groups is 4.8-7.9 mmol / g, and the specific surface area of the porous organic polymer with a high content of sulfonic acid groups is 54.3-160 m 2 / g.
[0015] Preferably, the pore volume of the porous organic polymer with a high content of sulfonic acid groups is 0.11-0.16 cm 3 / g, and the pore size of the porous organic polymer with a high content of sulfonic acid groups is 4.8-7.9nm.
[0016] In a third aspect, the present application provides an application of a porous organic polymer with a high content of sulfonic acid groups, using the following technical solution: As a general technical concept, the present application also provides the use of the above-mentioned porous organic polymer with a high content of sulfonic acid groups in the static adsorption and dynamic adsorption of ammonia.
[0017] In summary, the present application includes at least one of the following beneficial technical effects: 1. The porous organic polymer with a high content of sulfonic acid groups prepared in this application shows good performance and stable circulation capacity in the test of adsorption and separation of ammonia, and has excellent NH3 adsorption performance, selectivity and penetration ability, providing a solution for the selective elimination of low-concentration NH3; and providing a guarantee for the safe and efficient use of NH3 energy in various research fields.
[0018] 2. The porous organic polymer with a high content of sulfonic acid groups prepared in the present application maintains a porous structure, and a large number of strong acid sites are grafted on the benzene ring of the porous polymer, so that NH3 can interact freely with the super acid sites, allowing the active sites to play a maximum role.
[0019] 3. The porous organic polymer with a high content of sulfonic acid groups prepared in this application also has the characteristics of high porosity and large specific surface area. A large number of sulfonic acid groups are directly grafted on PDVB by chlorosulfonic acid. This method can not only obtain functionalized solid acid, but also distribute a large number of sulfonic acid groups on the porous organic polymer material, thereby increasing the ability to adsorb NH3.
[0020] 4. The porous organic polymer with high content of sulfonic acid groups prepared in this application has a large specific surface area, rich micro-mesoporous structure, excellent hydrophilicity and adjustable acid site content; in addition, the porous organic polymer has high-concentration and extremely strong superacid sites, which are evenly anchored on the inner surface of the sample, thereby improving its accessibility to guest molecules. The results show that the porous organic polymer has good NH3 high-precision adsorption and high-efficiency separation performance, and its NH3 capacity, breakthrough performance and cyclic stability are excellent among the adsorbents used in this field.
[0021] 5. The preparation method of the present application is simple, the reaction conditions are mild, the cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 N2 adsorption-desorption curves and pore size distribution diagrams of porous organic polymers with high content of sulfonic acid groups prepared in Examples 2 to 4 at -196°C; Figure 2 TEM and STEM images of PDVB-SO3H-1 prepared in Example 2; Figure 3 FIIR chart of PDVB-SO3H-1 prepared in Example 2; Figure 4 XPS graphs of porous organic polymers with high content of sulfonic acid groups prepared in Example 2 to Example 4, wherein a is PDVB-SO3H-1, b is PDVB-SO3H-2, and c is PDVB-SO3H-3; Figure 5 The static ammonia adsorption curve performance graphs of the porous organic polymers with high content of sulfonic acid groups prepared in Examples 2 to 4, wherein Figure A, Figure B, Figure C and Figure D are the static ammonia adsorption performance graphs of PDVB-SO3H-1, PDVB-SO3H-2 and PDVB-SO3H-3 at different temperatures (25°C, 50°C and 75°C) and the static ammonia adsorption performance graphs of PDVB-1, PDVB-2 and PDVB-3 at 25°C, respectively; Figure 6The static ammonia adsorption performance diagram of PDVB-SO3H-1 prepared in Example 2 and different comparative samples; Figure 7 Ternary gas mixture penetration diagrams (3.0% NH3 / 24.75% N2 / 72.25% H2) of porous organic polymers with high content of sulfonic acid groups prepared in Examples 2 to 4, wherein Figure A, Figure B, Figure C and Figure D are ternary gas mixture penetration diagrams of PDVB-1, PDVB-SO3H-1, PDVB-SO3H-2 and PDVB-SO3H-3, respectively; Figure 8 This is the in-situ NH3 adsorption infrared spectrum of PDVB-SO3H-1 prepared in Example 2. DETAILED DESCRIPTION
[0023] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0024] Example 1 Step 1: Disperse 0.075 g of ferric chloride in 25.0 mL of ethyl acetate containing 2.2 mL of deionized water and mix well, add 2.7 g of sodium styrene sulfonate and stir for 30 minutes to obtain a first mixed solution; Step 2: transferring the first mixed solution to a polytetrafluoroethylene-lined reactor for polymerization reaction at a reaction temperature of 220° C. for 8 hours to obtain a polymerization reaction product; Step 3: drying the polymerization product at 20° C. for 52 hours to obtain a solid product; Step 4: dispersing the solid product into 40 ml of dichloroethane solution to obtain a second mixed solution, adding 10 ml of chlorosulfonic acid to the second mixed solution under ice bath conditions and stirring for 15 hours to obtain a mixture A; Step 5: washing the mixture A with deionized water and filtering until the pH value of the mixture A reaches 5; when the pH value of the mixture A reaches 5, washing the mixture A with dichloroethane; Step 6: Dry the rinsed mixture A in a vacuum environment at 50° C. for 48 hours to obtain a porous organic polymer with a high content of sulfonic acid groups.
[0025] Example 2 Step 1: Disperse 0.065 g of azobisisobutyronitrile (AIBN) in 25.0 mL of tetrahydrofuran containing 2.0 mL of deionized water and mix well, add 2.5 mL of divinylbenzene (DVB) and stir for 100 minutes to obtain a first mixed solution; Step 2: transferring the first mixed solution to a polytetrafluoroethylene-lined reactor for polymerization reaction at a reaction temperature of 120° C. for 24 hours to obtain a polymerization reaction product; Step 3: drying the polymerization product at 25° C. for 48 hours to obtain a solid product, which is labeled as PDVB-1; Step 4: Disperse PDVB-1 in 40 ml of dichloroethane solution to obtain a second mixed solution, add 10 ml of chlorosulfonic acid to the second mixed solution under ice bath conditions and stir for 12 hours to obtain a mixture A; Step 5: washing the mixture A with deionized water and filtering until the pH value of the mixture A reaches 5; when the pH value of the mixture A reaches 5, washing the mixture A with dichloroethane; Step 6: Dry the rinsed mixture A in a vacuum environment at 80° C. for 24 hours to obtain a porous organic polymer with a high content of sulfonic acid groups, which is labeled as PDVB-SO3H-1.
[0026] Example 3 Step 1: Disperse 0.065 g of azobisisobutyronitrile (AIBN) in 25.0 mL of tetrahydrofuran and mix well, add 2.5 mL of divinylbenzene (DVB) and stir for 80 minutes to obtain a first mixed solution; Step 2: transferring the first mixed solution to a polytetrafluoroethylene-lined reactor for polymerization reaction at a reaction temperature of 220° C. for 8 hours to obtain a polymerization reaction product; Step 3: drying the polymerization product at 22° C. for 52 hours to obtain a solid product, which is labeled as PDVB-2; Step 4: Disperse PDVB-2 in 40 ml of dichloroethane solution to obtain a second mixed solution, add 10 ml of chlorosulfonic acid to the second mixed solution under ice bath conditions and stir for 14 hours to obtain a mixture A; Step 5: washing the mixture A with deionized water and filtering until the pH value of the mixture A reaches 5.5; when the pH value of the mixture A reaches 5.5, washing the mixture A with dichloroethane; Step 6: Dry the rinsed mixture A in a vacuum environment at 50° C. for 36 hours to obtain a porous organic polymer with a high content of sulfonic acid groups, which is labeled as PDVB-SO3H-2.
[0027] Example 4 Step 1: Disperse 0.065 g of azobisisobutyronitrile (AIBN) in 25.0 mL of ethyl acetate and mix well, add 2.5 mL of divinylbenzene (DVB) and stir for 90 minutes to obtain a first mixed solution; Step 2: transferring the first mixed solution to a polytetrafluoroethylene-lined reactor for polymerization reaction at a reaction temperature of 100° C. for 30 hours to obtain a polymerization reaction product; Step 3: drying the polymerization product at 22° C. for 48 hours to obtain a solid product, which is labeled as PDVB-3; Step 4: Disperse PDVB-3 in 40 ml of dichloroethane solution to obtain a second mixed solution, add 10 ml of chlorosulfonic acid to the second mixed solution under ice bath conditions and stir for 15 hours to obtain a mixture A; Step 5: washing the mixture A with deionized water and filtering until the pH value of the mixture A reaches 6; when the pH value of the mixture A reaches 6, washing the mixture A with dichloroethane; Step 6: Dry the rinsed mixture A in a vacuum environment at 60° C. for 24 hours to obtain a porous organic polymer with a high content of sulfonic acid groups, which is labeled as PDVB-SO3H-3.
[0028] Comparative Example 1 1. Weigh 0.08g NaAlO2 and add it to 10mL TEAOH (35%) and stir for 30 minutes, then add 7mL TEOS and 20mL deionized water and stir for 30 minutes, then add 7.5g PDADMAC and stir for 24 hours, transfer the above solution to a polytetrafluoroethylene-lined reactor, and after hydrothermal curing at 180°C for 3 days, filter and obtain a white solid, which is calcined at 550°C for 5 hours to obtain the primary product; 2. Disperse 1 g of the initial product in 1M NH4NO3 solution and perform ion exchange in an oil bath at 80°C for 4 hours, repeat three times. Calcinate at 550°C for 5 hours to obtain H-Beta molecular sieve, labeled H-Beta.
[0029] Comparative Example 2 1. Weigh 0.065g NaAlO2 and add it to 10mL TPAOH (35%) and stir for 30 minutes, then add 7mL TEOS and 20mL deionized water and stir for 30 minutes, then add 10g PDADMAC and stir for 24 hours, transfer the above solution to a polytetrafluoroethylene-lined reactor, and after hydrothermal curing at 180°C for 3 days, filter and obtain a white solid, which is calcined at 550°C for 5 hours to obtain the primary product; 2. Disperse 1 g of the initial product in 1 M NH4NO3 solution and perform ion exchange in an oil bath at 80°C for 4 hours, repeat three times. Calcinate at 550°C for 5 hours to obtain H-ZSM-5 molecular sieve, labeled as H-ZSM-5.
[0030] Performance analysis test characterization: X-ray diffraction (XRD) test was carried out on an X'Pert3 powder diffractometer, and the X-rays came from Cu Kα radiation The voltage and current were V=45kV and I=40mA, respectively. The internal nanostructure of the samples was studied on a FEI TecnaiG2F20 transmission electron microscope. The BET specific surface area and pore volume of various samples were evaluated on a Micromeritics TriStarⅡ3020 system, and degassed at 100°C for 12 hours before measurement. X-ray photoelectron spectroscopy (XPS) analysis was performed on a Thermo Fisher Scientific EscaLab 250Xi instrument, with the C1s peak of 284.8eV as the calibration standard. Fourier transform infrared spectroscopy was performed on a Nicolet-6700FT-IR to explore the molecular structure and functional groups of the samples. Test process: KBr was used as the background agent, and the test program was designed with 64 scans and a resolution of 4cm 1 and range 400-4000cm 1 .
[0031] Adsorption performance test: The NH3 absorption tank and buffer tank produced by Nantong Feiyu Petroleum Technology Development Co., Ltd. and the pressure sensor produced by Nanjing Tiancong Electric Co., Ltd. were used to evaluate the NH3 adsorption performance of the prepared solid acid adsorbent.
[0032] Gas permeation test: The NH3 permeation test was conducted on the AutoChem 2920 automatic adsorption instrument of Micromeritics, USA. Weigh 50 mg of sample, purge with high-purity argon at 150°C for 2 hours, then cool to a certain temperature and switch to NH3 mixed gas (3.0% NH3 / 24.75% N2 / 72.25% H2). First, the mixed gas does not pass through the sample tube, and the gas in the pipeline is tracked and recorded by the mass spectrometer (Hiden, HPR-20R&D). After the signal is stable, switch the gas path to pass through the sample, and continue to track and record the mixed gas passing through the adsorbent with the mass spectrometer, and stop recording after the gas components return to the concentration of the raw gas.
[0033] The texture parameters of PDVB-x (PDVB-1, PDVB-2, PDVB-3) and PDVB-SO3H-x (PDVB-SO3H-1, PDVB-SO3H-2, PDVB-SO3H-3) obtained in Example 2 to Example 4 are analyzed as shown in Table 1: Table 1 Texture parameters of PDVB-x and PDVB-SO3H-x a Surface area calculated by BET equation; b Total pore volume calculated by DFT method; c Pore size inferred from pore size distribution; d The hydrogen ion exchange strength measured after sodium ion exchange.
[0034] Analyzing the data in Table 1, we can see that: The porous organic polymers with high content of sulfonic acid groups prepared in Examples 2 to 4 have a sulfonic acid group content ranging from 4.8 to 7.9 mmol / g and a specific surface area ranging from 54.3 to 160 m 2 / g, pore volume range is 0.11-0.16cm 3 / g, and the pore size range is 4.8-7.9nm.
[0035] Figure 1 The N2 adsorption-desorption curve and pore size distribution diagram of the porous organic polymer with high content of sulfonic acid groups prepared in Examples 2 to 4 at -196°C, and the corresponding texture parameters are shown in Table 1; Figure 1 It can be found that all PDVB-x have obvious hysteresis loops in the range of 0.4-0.95, which indicates that PDVB-x has obvious mesoporous structure. Correspondingly, various PDVB-x show different BET specific surface areas, pore volumes and pore sizes ranging from 301.8 to 597 m 2 / g, 0.22-1.01cm 3 / g and 3.9-9.2nm; among them, after the introduction of sulfonic acid groups, the specific surface area of PDVB-SO3H-x decreased significantly, and the pore volume and pore size also showed a downward and decreasing trend. The specific BET specific surface area, pore volume and pore size were 54-164.4m 2 / g, 0.11-0.16cm 3 / g and 4.8-7.9nm, which may be caused by the collapse of the skeleton during the sulfonation process and the occupation of the mesoporous channels by the sulfonic acid groups. +After ion exchange, it was found that PDVB-SO3H-x had a strong ion exchange strength, specifically 4.8-7.9 mmol / g, which also means that PDVB-SO3H-x has a higher sulfonic acid group content.
[0036] Figure 2 TEM and STEM images of PDVB-SO3H-1 prepared in Example 2 are shown in FIG. Figure 2 As shown in the figure, PDVB-SO3H-1 has abundant wormhole-like mesoporous structure characteristics. Further magnification shows that PDVB-SO3H-1 also has a large number of micropores, which is consistent with the results of N2 adsorption-desorption curve analysis. Figure 2 (EH) shows the STEM image and element distribution map of PDVB-SO3H-1, which accurately reflects the nanoporous structure characteristics and element distribution of the sample. It is worth noting that rich microporous structures and good distribution of C, O and S were found in PDVB-SO3H-1, which further confirms that a large number of sulfonic acid groups were successfully introduced into PDVB-SO3H-1.
[0037] Figure 3 The FIIR diagram of PDVB-SO3H-1 prepared in Example 2 is as follows: Figure 3 As shown, at 3382cm -1 A clear broad peak can be observed near 860-1700 cm -1 There are many complex signal peaks in the range. In order to deeply analyze the properties of these peaks and the series of peaks related to -SO3H, the intercept wavelength is 860–1700cm -1 ,like Figure 3 As shown in B: at 889, 1010, 1176 and 1366 cm -1 There are four more characteristic peaks nearby, which are the stretching vibration signals of symmetric S-OH bond, asymmetric S=O bond, asymmetric SO bond and symmetric S=O bond, indicating that sulfonic acid group was successfully introduced into PDVB-SO3H-1.
[0038] Figure 4 The XPS graphs of porous organic polymers with high content of sulfonic acid groups of Example Preparation 2 to Example 4 are shown in Figure 1, where a is PDVB-SO3H-1, b is PDVB-SO3H-2, and c is PDVB-SO3H-3. Figure 4As shown in the XPS spectrum of PDVB-SO3H-x, a series of signals related to C, O and S can be found, indicating that the sulfonic acid group has been successfully introduced into the porous polymer. In addition, after peak fitting of the S2p spectrum, it was found that all PDVB-SO3H-x had two obvious characteristic peaks at 168.5eV and 169.7eV, which can be interpreted as the characteristic peaks corresponding to SC and SO bonds through signal attribution analysis.
[0039] Figure 8 This is the in-situ NH3 adsorption infrared spectrum of PDVB-SO3H-1 prepared in Example 2. Figure 8 It can be seen that with the extension of NH3 adsorption time, after the sample has been adsorbed for 10 minutes, the characteristic peaks of the functional groups corresponding to the ammonia reaction gradually begin to appear, such as 1159cm -1 、1319cm -1 、1400cm -1 、1500cm -1 、1543cm -1 and 1626cm -1 There are obvious peak changes in the signal bands, which are related to the functional groups of the porous polymer solid acid after adsorption of ammonia and the derived NH4 + The research found that 1319cm -1 and 1626cm -1 The signal band at 1543 cm -1 The signal band at is explained as the NH4 formed by the H provided by the B acid on PDVB-SO3H-1 during the reaction with NH3 + , indicating that the NH3 and -SO3H superacid sites in PDVB-SO3H-1 play the roles of electron donor and acceptor, respectively, leading to their acid-base interaction during NH3 adsorption.
[0040] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a porous organic polymer with a high content of sulfonic acid groups, characterized in that: The following steps are involved: S1, mixing the crosslinking agent monomer, the initiator and the first solvent to obtain a first mixed solution; S2, transferring the first mixed solution to a polytetrafluoroethylene-lined reactor for polymerization reaction to obtain a polymerization reaction product; S3, drying the polymerization product at the first temperature to obtain a solid product; S4, dispersing the solid product in a dichloroethane solution to obtain a second mixed solution, adding chlorosulfonic acid to the second mixed solution under ice bath conditions and stirring to obtain a mixture A; S5, washing the mixture A with deionized water and filtering until the pH value of the mixture A is 5-6; when the pH value of the mixture A reaches 5-6, washing the mixture A with dichloroethane; S6. Drying the rinsed mixture A under vacuum to obtain a porous organic polymer with a high content of sulfonic acid groups.
2. The method for preparing a porous organic polymer with a high content of sulfonic acid groups according to claim 1, characterized in that: In step S1, the crosslinking agent monomer is at least one of divinylbenzene and sodium styrene sulfonate; the initiator is at least one of ferric chloride and azobisisobutyronitrile; and the first solvent is at least one of ethyl acetate and tetrahydrofuran.
3. The method for preparing a porous organic polymer with a high content of sulfonic acid groups according to claim 1, characterized in that: In step S1, the mixing and stirring time is 30-100 minutes.
4. The method for preparing a porous organic polymer with a high content of sulfonic acid groups according to claim 1, characterized in that: In step S2, the reaction temperature of the polymerization reaction is 100-220° C., and the reaction time of the polymerization reaction is 8-30 hours.
5. The method for preparing a porous organic polymer with a high content of sulfonic acid groups according to claim 3, characterized in that: In step S3, the first temperature is 20-25°C, and the drying time is 48-52 hours.
6. The method for preparing a porous organic polymer with a high content of sulfonic acid groups according to claim 1, characterized in that: In step S4, the stirring time is 12-15 hours.
7. The method for preparing a porous organic polymer with a high content of sulfonic acid groups according to claim 1, characterized in that: In step S4, the drying temperature is 50-80°C.
8. A porous organic polymer having a high content of sulfonic acid groups, characterized in that: The porous organic polymer with a high content of sulfonic acid groups is prepared by the method for preparing a porous organic polymer with a high content of sulfonic acid groups according to any one of claims 1 to 7, characterized in that the content of sulfonic acid groups in the porous organic polymer with a high content of sulfonic acid groups is 4.8-7.9 mmol / g, and the specific surface area of the porous organic polymer with a high content of sulfonic acid groups is 54.3-160 m 2 / g.
9. A porous organic polymer with a high content of sulfonic acid groups according to claim 8, characterized in that: The pore volume of the porous organic polymer with a high content of sulfonic acid groups is 0.11-0.16 cm 3 / g, and the pore size of the porous organic polymer with a high content of sulfonic acid groups is 4.8-7.9 nm.
10. Use of a porous organic polymer with a high content of sulfonic acid groups as claimed in any one of claims 8 to 9 in static adsorption and dynamic adsorption of ammonia.